MORPHOLOGICAL AND MORPHOMETRICAL CHANGES THAT OCCUR IN ENDOMETRIUM OF AWASI EWES DURING DIFFERENT STAGES OF PREGNANCY - A. M. Elias (Basrah Journal of Veterinary Research)
Sixteen utri of Awasi sheep at different stages of pregnancy were used in this study .The intercaruncular surface epithelium was pseudostratified at the early stage of pregnancy and then changed gradually to simple columnar after day 50 0f pregnancy. At day 118 it become low columnar or simple cuboidal and decreased in height . The glandular epithelium was mainly simple columnar and showed high secretory activity during the studied of pregnancy stages. The glandular diameter and their lumen was increased with the advancement of pregnancy . The gland showed saculation at late stages of pregnancy .